2012
DOI: 10.2967/jnumed.111.098681
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging–Based Evaluation of Hepatobiliary Transport in Humans with (15R)-11C-TIC-Me

Abstract: It is well accepted that drug transporters play a pivotal role in hepatobiliary excretion of anionic drugs, in which drug-drug interactions and genetic polymorphisms are known to cause variations. However, PET probes for in vivo functional characterization of these transporters have not been established yet. We used PET to investigate hepatic uptake and subsequent canalicular efflux of 11 C-labeled (15R)-16-m-tolyl-17,18,19,20-tetranorisocarbacyclin methyl ester [(15R)-11 C-TIC-Me)] in healthy subjects. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 31 publications
2
90
1
Order By: Relevance
“…Recently, to non-invasively perform the real-time measurement of the tissue concentration of drugs, several kinds of positron emission tomography (PET) probes for evaluating OATP function have been created and characterized in rodents and humans. [70][71][72][73] By using the time profile data for tissue concentration as well as the plasma concentration of drugs to optimize the model parameters, we can further increase the reliability of a PBPK model. Another strategy is to create methods for extracting multiple candidate sets of model parameters which can reproduce a limited number of clinical data.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, to non-invasively perform the real-time measurement of the tissue concentration of drugs, several kinds of positron emission tomography (PET) probes for evaluating OATP function have been created and characterized in rodents and humans. [70][71][72][73] By using the time profile data for tissue concentration as well as the plasma concentration of drugs to optimize the model parameters, we can further increase the reliability of a PBPK model. Another strategy is to create methods for extracting multiple candidate sets of model parameters which can reproduce a limited number of clinical data.…”
Section: Resultsmentioning
confidence: 99%
“…CsA, rifampin, and gemfibrozil were used as the strong (CsA and rifampin) or weak (gemfibrozil) OATP1B1 inhibitors in this study because they showed substrate-dependent OATP1B1 inhibition with 6-to 14-fold difference in the K i values when E 2 G, E 1 S, and BSP were used as in vitro test probes (Izumi et al, 2013), and administration of the inhibitors has caused clinical DDIs with OATP1B1 substrate drugs (Shitara et al, 2013b). In fact, inhibition of hepatic uptake by rifampin was demonstrated in healthy subjects by positron emission tomography using 15R-[ 11 C]TIC as an OATP substrate (Takashima et al, 2012). The K i values of CsA, rifampin, and gemfibrozil for the clinically used substrate drug uptake showed 6.3-, 3.4-, and 26-fold variations depending on the substrates, respectively (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic polymorphisms of SLCO1B1 are associated with interindividual variation in the plasma concentrations of 3-hydroxymethylglutarylCoA reductase inhibitors (statins) (Shitara and Sugiyama, 2006) and adverse event rates during simvastatin therapy (Link et al, 2008). In clinical situations, DDIs involving OATP substrate drugs and cyclosporine A (CsA) or a single dose of rifampin are considered to be attributable to the inhibition of OATP1B1 and its closely-related isoform, OATP1B3 (Shitara et al, 2003;Maeda et al, 2011;Takashima et al, 2012). Based on the accumulated evidence, OATP1B1 has been widely recognized as a clinically important transporter, and the evaluation of OATP1B1-mediated DDI potential of drug candidates is crucial in the drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data on tissue concentrations obtained by advanced imaging methods [33,99], in conjunction with mechanistic PBPK modeling, is envisaged as a powerful tool to improve predictability and understanding of implications of transportermediated tissue distribution and interactions.…”
Section: Hepatobiliary Transporter Mediated Drug-drug Interactionsmentioning
confidence: 99%